Caracterización y extracción de aceite de semillas de calabaza para la producción de un batido funcional (2020)
Pumpkin seed oil has excellent anti-inflammatory and antioxidant properties, as well as a high content of unsaturated fatty acids. However, pumpkin seed oil is not generally consumed because pumpkin seeds are usually discarded. Pumpkin seed oil extraction was done via cold press and it was physicochemically characterized; results indicated a density of 0.9175 g/ml, a humidity 0.3597¿0.047%, a refraction index of 1.4732, an acid, saponification, iodine and peroxide values of 7.6530 ¿0.183 mg KOH/ g oil, 175.8037¿4.504 mg KOH/g oil, 155.5385¿2.82 g I2/100 g oil, 4.1008¿0.425 meq O2/kg oil respectively. It was determined that pumpkin seed oil possesses the favourable qualities of an edible oil. A milkshake with three different concentrations of oil (2%, 4% and 6% w/w) was prepared. It was classified as a non-Newtonian pseudo plastic fluid. Stability tests were carried out for a time period of 15 minutes, an acceptability test and a CATA (Check all that apply) questionnaire took place, which were generally positive for the lower concentration milkshakes.